Odpowiedź :
Obliczenia
[tex]\frac{x}{3}[/tex]-[tex]\frac{1}{2}[/tex]=3x-[tex]\frac{x-2}{4}[/tex]
4x-6=36x-3(x-2)
4x-6=36x-3x+6
4x-6=33x+6
-29x=12
x=-[tex]\frac{12}{29}[/tex]
Sprawdzenie
[tex]\frac{\frac{-12}{29} }{3}[/tex]-[tex]\frac{1}{2}[/tex]=3(-[tex]\frac{12}{29}[/tex])-[tex]\frac{-\frac{12}{29}-2 }{4}[/tex]
-[tex]\frac{4}{29}[/tex]-[tex]\frac{1}{2}[/tex]=-[tex]\frac{36}{29}[/tex]-[tex]\frac{\frac{-70}{29} }{4}[/tex]
-[tex]\frac{37}{58}[/tex]=-[tex]\frac{36}{29}[/tex]+[tex]\frac{35}{58}[/tex]
-[tex]\frac{37}{58}[/tex]=-[tex]\frac{37}{58}[/tex]
prawda